A study of the provision for and use by library managers of management information from computer-based library systems in academic libraries - Akbar Hakim Haji Harun (2010)
This study examined the current management information provision from computer-based library systems for library managers in academic libraries, putting into focus the adequacy of such provision. In addition, the study also looked at the use of and reliance on the statistical information generated from these automated library systems by library managers, in relation to the latter's level of management and decision-making process. The future developments of management information systems in academic libraries was also considered.